Incidencia de la cultura y educación ambiental en los estudiantes del colegio Dr. José María Velasco Ibarra del cantón El Guabo con respecto a la protección y conservación de la naturaleza, período lectivo 2013-2014 - Pesántez Crespo, Marjuri Lucía (Machala : Universidad Técnica de Machala, 2014)
In the El Guabo Canton have not implemented environmental education programs short medium or long term. In this situation the absence of these projects campaigns, culture and environmental education will continue generating contributing environmental problems with local environmental deterioration, requiring that education involving students in environmental education processes is promoted, to ensure the quality of life of people and the planet. This research was related to the realization of a diagnosis to know the impact of culture and environmental Education of college students Dr. José Maria Velasco Ibarra canton Guabo regarding the protection and conservation of nature and environment frequenting campus.
Keywords: CULTURA; EDUCACION; AMBIENTAL; PROTECCION; CONSERVACION; NATURALEZA